Development of Interactive Learning Videos to Increase Learning Motivation in Graphic Design Lessons in Vocational Schools - Muhammad Arief Rohman; Fitria Nur Hasanah; Rahmania Sri Untari Untari (Proceedings of The ICECRS, 2020)
This study aims to find out the increase in learning motivation through the use of Interactive Learning Videos Graphic Design students of class X TKJ in SMK. The research method used is R & D research using the ADDIE development model. The sample is class X TKJ in SMK Muhammadiyah 1 Taman. Developed media declared 79% feasible with high criteria as a medium can be used for research. Based on the results of the use of interactive learning video media makes a difference in student motivation. Before using interactive learning videos, the results of the students with 56-70 grade range (medium) are being categorized C. Using interactive learning videos; students get the results to a range of grades 71-85 with good qualifications and categorized B. They also get the results of the range of grades 86-100 with very good qualifications and categorized A. In conclusion; the interactive learning video graphic design is feasible to be used as a learning medium for students of class X TKJ in SMK Muhammadiyah 1 Taman. With the use of interactive learning videos there is an increase in motivation class X TKJ to learn on graphic design subjects.